Saccharification of a Potential Bioenergy Crop, Phragmites australis (Common Reed), by Lignocellulose Fractionation Followed by Enzymatic ydrolysis at Decreased Cellulase Loadings - Sathitsuksanoh, N.; Zhu, Z.; Templeton, N.; Rollin, J.A.; Harvey, S.P.; Percival Zhang, Y.H.
Cost-effective biological saccharification of nonfood lignocellulosic biomass is vital to the establishment of a carbohydrate economy. Phragmites australis (common reed)is regarded as an invasive perennial weed with a productivity of up to 18-28 tons of dry weight per acre per year. We applied the cellulose solventand organic solvent-based lignocellulose fractionation (COSLIF)to the stems and leaves of Phragmites and optimized the pretreatment conditions (e.g., temperature, reaction time, and biomass moisture content)through response surface methodology (RSM). The optimal pretreatment conditions were 85